2012
DOI: 10.1097/pcc.0b013e31820aba48
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of interrupted versus continuous sedative infusions in ventilated children

Abstract: The length of mechanical ventilation, duration of intensive care unit stay, total dose of midazolam, and average calculated cost of the therapy were significantly reduced in the interrupted as compared to the continuous group of sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 15 publications
2
74
2
5
Order By: Relevance
“…Gupta et al demonstrated a decrease in duration of ventilatory support, leading to a reduction from 13.01 days in the control group to 8.4 days in the daily interruption group (p=0.028); shorter length of ICU stay, from 14 days in the control group to 11 days in the intervention group (p=0.023); lower doses of midazolam used in the daily interruption group (p=0.002), implicating lower hospitalization costs without an increase in the number of adverse events. 35 Another study, by Verlaat et al, showed similar results, with a significant decrease in sedative and analgesic agents used; less time of mechanical ventilation and decreased length of ICU stay with no increase in the numbers of adverse events. 36 A recent study by Vet NJ et al, however, did not show much benefit in the use of daily interruption strategies to shorten the duration of mechanical ventilation or hospitalization, or the quantities of sedatives used, with the use of these strategies potentially associated with a higher 30-day mortality rate, without explaining the reasons behind this fact.…”
Section: Resultssupporting
confidence: 54%
“…Gupta et al demonstrated a decrease in duration of ventilatory support, leading to a reduction from 13.01 days in the control group to 8.4 days in the daily interruption group (p=0.028); shorter length of ICU stay, from 14 days in the control group to 11 days in the intervention group (p=0.023); lower doses of midazolam used in the daily interruption group (p=0.002), implicating lower hospitalization costs without an increase in the number of adverse events. 35 Another study, by Verlaat et al, showed similar results, with a significant decrease in sedative and analgesic agents used; less time of mechanical ventilation and decreased length of ICU stay with no increase in the numbers of adverse events. 36 A recent study by Vet NJ et al, however, did not show much benefit in the use of daily interruption strategies to shorten the duration of mechanical ventilation or hospitalization, or the quantities of sedatives used, with the use of these strategies potentially associated with a higher 30-day mortality rate, without explaining the reasons behind this fact.…”
Section: Resultssupporting
confidence: 54%
“…In children, continuous sedation is associated with longer mechanical ventilation, 31 whereas daily interruption of sedation is associated with shorter mechanical ventilation. 32 Altered mental status and absence of airway reflexes at the time of extubation are associated with extubation failure in children, 33 but inadequate sedation is also associated with unplanned extubation and post-extubation stridor. 34 The majority of our respondents consider sedation an important element in extubation readiness but do not use a formal standardized sedation score; instead they use their own clinical judgment.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this current study could simply reflect the strong history in the Netherlands of good sedation practice including a relative sparing use of sedatives. This is supported by the relatively low dose of midazolam used compared to a previous paediatric study [7]. One conclusion is that recovery from sedation relates to the overall cumulative ''sedation burden'' and that minimizing the exposure, with effective behavioural scoring linked to delivery, optimizes recovery irrespective of DSI and other factors.…”
mentioning
confidence: 88%
“…The value of DSI [5][6][7] remains unclear. The results of this current study could simply reflect the strong history in the Netherlands of good sedation practice including a relative sparing use of sedatives.…”
mentioning
confidence: 99%